Lightning Caused Multiple Deaths: Lethality of Taking Shelter in Unprotected Buildings - Gomes C.; Izadi M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Costs; Lightning; Lightning protection; MATLAB; Roofs; Electric field distributions; Human safety; injuries; Lightning currents; Low costs; Return stroke current; Simulation of lightnings; under-privileged; Walls (structural partitions)